2005
DOI: 10.1246/bcsj.78.1032
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, Crystal Structure, and Magnetic Properties of Mn12 Single-Molecule Magnets with Naphthalenecarboxylate Bridges, [Mn12O12(O2CC10H7)16(H2O)4] and Their Tetraphenylphosphonium Salts

Abstract: The preparation and physical characterization are reported for three Mn12 single-molecule magnets (SMMs) having naphthalenecarboxylate bridges, [Mn12O12(2-nc)16(H2O)4] (1, 2-ncH = 2-naphthalenecarboxylic acid), its Ph4P+ salt (2) and [Mn12O12(1-nc)16(H2O)4] (3, 1-ncH = 1-naphthalenecarboxylic acid). Complex 1·2CH2Cl2·4.5H2O crystallizes in the monoclinic space group C2/c, with cell dimensions at −160 °C of a = 28.524 Å, b = 17.819 Å, c = 36.058 Å, β = 92.399°, and Z = 4. The X-ray structure analysis of 1·2CH2C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Gerbier et al utilized this approach by introducing spin-carrying carboxylate groups onto the Mn 12 molecule using 1-[N-t-butyl-N-(oxyl)amino]-4-benzoic acid radicals, which coupled antiferromagnetically to the [Mn 12 O 12 ] core [ 39 ]. Bian et al prepared naphthalene-carboxylate derivatives that assembled two-dimensionally via π-π interactions [ 47 ], and Willemin et al made methacrylate derivatives to produce chemically and thermally stable nanocomposites [ 48 ]. Coronado et al have reported the way for the synthesis of the polycationic form of Mn with an S T = 11 ground state using betaine hexafluorophosphate salt (see Figure 2 b) [ 49 ].…”
Section: Characteristics and Main Representatives Of Smmsmentioning
confidence: 99%
“…Gerbier et al utilized this approach by introducing spin-carrying carboxylate groups onto the Mn 12 molecule using 1-[N-t-butyl-N-(oxyl)amino]-4-benzoic acid radicals, which coupled antiferromagnetically to the [Mn 12 O 12 ] core [ 39 ]. Bian et al prepared naphthalene-carboxylate derivatives that assembled two-dimensionally via π-π interactions [ 47 ], and Willemin et al made methacrylate derivatives to produce chemically and thermally stable nanocomposites [ 48 ]. Coronado et al have reported the way for the synthesis of the polycationic form of Mn with an S T = 11 ground state using betaine hexafluorophosphate salt (see Figure 2 b) [ 49 ].…”
Section: Characteristics and Main Representatives Of Smmsmentioning
confidence: 99%
“…So far, this has been at an evolutionary stage with the current focus mainly on understanding the factors that determine the crystal packing as well as exploring relevant properties [3,[7][8][9][10][11]. Among various ligands, the versatile carboxylic acid ligands exhibiting diverse coordination modes, especially benzene-based and naphthalene-based carboxylic acids have been employed and well documented in the preparations of various carboxylato-containing Mn II metalorganic complexes [12][13][14][15][16][17][18][19][20][21][22]. Some of these are benzoic acid [12][13][14][15][16][17][18][19][20][21], naphthalene-2-carboxylic acid [22], and naphthalene-1-carboxylic acid [23].…”
Section: Introductionmentioning
confidence: 99%